SYSTEMATIZATION OF THE RECOVERY OF ADAPTIVE BODY RESERVES IN QUALIFIED MMA ATHLETES DURING THE SHORT-TERM PERIOD BETWEEN CONSECUTIVE COMPETITIONS - Shtefiuk, I.; Moseichuk, Y.; Chernozub, A. (Rehabilitation and Recreation, 2025)
The aim is to study the systematization features of restoring adaptive body reserves of qualified MMA athletes in the short-term period between competitions. Material and methods. The Ukrainian junior MMA team participated in the study. The team consisted of 16 men aged 17 ± 0.87 years. 8 team representatives used mainly the striking fighting style and the other 8 athletes had a wrestling style. The experience of MMA training was 5 ± 0.58 years. The study used control testing methods, heart rate variability assessment, and biochemical blood analysis, including creatine phosphokinase and lactate dehydrogenase measurements. Registration of RR interval signals and biochemical studies were carried out in a state of rest before and after performing test loads during three stages. Results. During short-term periods of training and recovery between a series of competitions, the qualified MMA athletes showed different types of adaptive and compensatory reactions to test loads. Before the first competitions, there was an increase in the influence of autonomous regulation of the heart rhythm and a balance of vagal-sympathetic tone mechanisms in response to test loads. The creatine phosphokinase activity grew in the blood of the striking-style athletes, but wrestling-style athletes increased only the LDH level. After the first competitions, there was a shift in the vegetative balance from the side of parasympathetic and sympathetic regulation in response to test loads in athletes of both styles. Strengthening the central circuit of sinus rhythm regulation in response to loads that previously decreased the sympathetic tone may indicate compensatory reactions and lower adaptive reserves. The simultaneous rise in both enzymes in the blood of certain wrestling-style athletes under high-intensity test loads, utilizing the creatine phosphokinase energy supply mechanism, suggests compensatory reactions. Adjustments in the load regime and energy supply mechanism affect restoring adaptive reserves during the short-term preparation period between competitions. These changes in athletes’ bodies reflect the balance of vagal-sympathetic tone mechanisms and fluctuations in CPK and LDH enzyme levels in the blood in response to a stressful stimulus. Conclusions. The practical significance of implementing the proposed system for monitoring adaptive reserves and adjusting training loads in MMA athletes preparing for competitions with short recovery periods has been confirmed. The developed algorithm for structuring training models in pre-competition mesocycles effectively facilitates the recovery of athletes with depleted adaptive reserves. The findings of the study confirm the effectiveness of using HRV indicators and biochemical blood analysis to evaluate the adaptive reserves of qualified athletes.